Estratégias multiplataforma na franquia do portal G1: a influência do jornalismo de portal na produção do G1 em 1 minuto - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This monography has got as a theme multiplatform strategies developed by franchises within digital native media. The research was conduct with the general aim of identifying if there is influence of portal journalism in the audiovisual production of G1 em 1 Minuto, under the condition of jornalistic franchise. For that, four chapters were structured, supported by author’s concepts about these topic. In the first chapter, a definition of Web journalism is presented, showing its generation and characteristics. In the second chapter, the potencialities of the journalism made via portals are exposed, searching its definitions and highlightable aspects such as the development of audiovisual journalism through these means, being the portals, digital natives. The contexts were those different productions were fulfilled is presented in chapter three, in which the franchise movements within the digital natives are explained. Lastly, in the fourth chapter is accomplished, starting by exploratory research, the analysis of G1 and G1 em 1 Minuto, whilst franchise. Also, four editions from a day of the bulletin are analysed, trying to compreende the production process of G1 em 1 Minuto. Through the observations and analysis it was possible to verify that its movement may be considered as the journalistic franchise formation, having the audiovisual under influence of the portal journalism in many different aspects.
Keywords: Jornalismo; Jornais eletrônicos; Central Globo de Jornalismo; Journalism; Electronic Newspapers; CNPQ::CIENCIAS SOCIAIS APLICADAS